Occurrence of the mcr-1 Colistin Resistance Gene and other Clinically Relevant Antibiotic Resistance Genes in Microbial Populations at Different Municipal Wastewater Treatment Plants in Germany - Hembach, Norman; Schmid, Ferdinand; Alexander, Johannes; Hiller, Christian; Rogall, Eike T.; Schwartz, Thomas (Frontiers in Microbiology, 2017)
Seven wastewater treatment plants (WWTPs) with different population equivalents and catchment areas were screened for the prevalence of the colistin resistance gene mcr-1 mediating resistance against last resort antibiotic polymyxin E. The abundance of the plasmid-associated mcr-1 gene in total microbial populations during water treatment processes was quantitatively analyzed by qPCR analyses. The presence of the colistin resistance gene was documented for all of the influent wastewater samples of the seven WWTPs. In some cases the mcr-1 resistance gene was also detected in effluent samples of the WWTPs after conventional treatment reaching the aquatic environment. In addition to the occurrence of mcr-1 gene, CTX-M-32, blaTEM, CTX-M, tetM, CMY-2, and ermB genes coding for clinically relevant antibiotic resistances were quantified in higher abundances in all WWTPs effluents. In parallel, the abundances of Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli were quantified via qPCR using specific taxonomic gene markers which were detected in all influent and effluent wastewaters in significant densities. Hence, opportunistic pathogens and clinically relevant antibiotic resistance genes in wastewaters of the analyzed WWTPs bear a risk of dissemination to the aquatic environment. Since many of the antibiotic resistance gene are associated with mobile genetic elements horizontal gene transfer during wastewater treatment can´t be excluded.